Integrated transcriptional‐phenotypic analysis captures systemic immunomodulation following antiangiogenic therapy in renal cell carcinoma patients. Issue 6 (20th June 2021) - Rinchai, Darawan; Verzoni, Elena; Huber, Veronica; Cova, Agata; Squarcina, Paola; De Cecco, Loris; de Braud, Filippo; Ratta, Raffaele; Dugo, Matteo; Lalli, Luca; Vallacchi, Viviana; Rodolfo, Monica; et al.
Abstract: Background: The combination of immune checkpoint blockade (ICB) with standard therapies is becoming a common approach for overcoming resistance to cancer immunotherapy in most human malignancies including metastatic renal cell carcinoma (mRCC). In this regard, insights into the immunomodulatory properties of antiangiogenic agents may help designing multidrug schedules based on specific immune synergisms. Methods: We used orthogonal transcriptomic and phenotyping platforms combined with functional analytic pipelines to elucidate the immunomodulatory effect of the antiangiogenic agent pazopanib in mRCC patients. Nine patients were studied longitudinally over a period of 6 months. We also analyzed transcriptional data from The Cancer Genome Atlas (TCGA) RCC cohort (N = 571) to assess the prognostic implications of our findings. The effect of pazopanib was assessed in vitro on NK cells and T cells. Additionally, myeloid‐derived suppressor (MDSC)‐like cells were generated from CD14 + monocytes transfected with mimics of miRNAs associated with MDSC function in the presence or absence of pazopanib. Results: Pazopanib administration caused a rapid and dramatic reshaping in terms of frequency and transcriptional activity of multiple blood immune cell subsets, with a downsizing of MDSC and regulatory T cells in favor of a strong enhancement in PD‐1 expressing cytotoxic T and Natural Killer effectors. These changes were paired with an increase of the expression of transcripts reflecting activation of immune‐effector functions. This immunomodulation was marked but transient, peaking at the third month of treatment. Moreover, the intratumoral expression level of a MDSC signature (MDSC INT) was strongly associated with poor prognosis in RCC patients. In vitro experiments indicate that the observed immunomodulation might be due to an inhibitory effect on MDSC‐mediated suppression, rather than a direct effect on NK and T cells. Conclusions: The marked but transient nature of this immunomodulation, peaking at the third month of treatment, provides the rationale for the use of antiangiogenics as a preconditioning strategy to improve the efficacy of ICB. Abstract :